Utilization of Accreditation in the Total Quality Management of Madrasah Education - Mansur, Mansur; Mardiyah, Mardiyah; Khan, Abdul Latif (Maharot : Journal of Islamic Education, 2023)
The accreditation process evaluates schools and madrasahs to determine their eligibility. It is carried out by an independent and professional institution, such as BAN S/M in Indonesia, which provides recognition to these educational institutions. Accreditation aims to establish sustainable quality assurance for primary and secondary education. Educational institutions are expected to continuously improve their quality to gain community trust. This expectation arises from the understanding that quality control and assurance are essential for meeting educational standards and emphasizing the responsibilities of educators and staff, aligned with Total Quality Management (TQM) principles. This qualitative research study focuses on a case study conducted at Madrasah Aliyah Nurul Huda Masaran (MA Nurul Huda Masaran) from January 1 to March 31, 2023. The research objectives encompass the entire MA Nurul Huda community, including institutions, educators, staff, and students. Data collection methods include observation, interviews, and documentation, resulting in primary and secondary data categories. The data analysis process involves techniques such as data reduction, presentation, and verification. The research findings indicate that accreditation activities lead to improvements in TQM, specifically in graduate quality, the learning process, educator quality, and madrasah management.